Analisis Pelaksanaan Layanan Perawatan Dukungan dan Pengobatan (PDP) HIV–AIDS di Rumah Sakit Daerah Balung - Rintan Illahi Wahyu; Faiqatul Hikmah; Rossalina Adi Wijayanti; Niyalatul Muna (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2020)
The implementation of HIV - AIDS Support and Treatment (PDP) Care Services at Balung Regional General Hospital is not yet in line with the target. This is evidenced by the number of PLHIV fulfilling the requirements to start treatment, not all of them are taking ARV treatment, so an analysis of these services is needed. The purpose of this study was to analyze the implementation of HIV - AIDS support and treatment (PDP) care services at Balung Regional Hospital. This type of research is qualitative, using interview, observation and documentation data collection methods. Informants in this study were 1 doctor, 1 counselor and 1 nurse and 8 ODHA This type of research is qualitative, the result of this study is an analysis of the implementation of HIV-AIDS support and treatment care services using 4M indicators (man, method, material and mechine). The results of the study were obtained that the analysis of PDP services based on the aspects of man, namely the availability of resources in the service is lacking and knowledge of HIV – AIDS  related to HIV - AIDS is still low, aspects of the method that there are SOP but there is no clear jobdesc, material aspects there is a medical record used for know the development of ODHA, but the officers in filling it are still incomplete, aspects of the mechine are available tools that are used to assist the process of conducting maintenance services such as general inspection tools and SIHA. Efforts to resolve the problem above so that the Balung Regional General Hospital for submitting letters to the Health Office regarding job analysis, the role of the medical recorder for checking the filing of ODHA medical record files and for problems of low knowledge of HIV – AIDS can be done by counseling in privacy.